1997
DOI: 10.1046/j.1365-2249.1997.d01-899.x
|View full text |Cite
|
Sign up to set email alerts
|

Febrile infection changes the expression of IgG Fc receptors and complement receptors in human neutrophils in vivo

Abstract: SUMMARYWe have examined the expression of the IgG Fc receptors (FcRI, FcRII, FcRIII) and complement receptors (CR1, CR3) in neutrophils from 42 patients with febrile bacterial infection, 20 patients with febrile viral infection and 69 non-febrile healthy individuals. Using receptor-specific MoAbs and immunofluorescence flow cytometry the relative fluorescence intensity (as a measure of receptor number) and the proportion of receptor-positive cells were determined in peripheral blood neutrophils exposed to min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 36 publications
0
42
1
Order By: Relevance
“…Earlier studies indicated that adult PB PMN expressed very low levels of Fc␥RI (35), a result consistent with our data. The up-regulation of Fc␥RI expression on PMN was observed for patients with febrile bacterial infections (31) and was shown to be induced by IFN-␥ (21,50). Human inflamed gingival tissue contains ␥␦ T cells expressing IFN-␥ mRNA (34,61).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies indicated that adult PB PMN expressed very low levels of Fc␥RI (35), a result consistent with our data. The up-regulation of Fc␥RI expression on PMN was observed for patients with febrile bacterial infections (31) and was shown to be induced by IFN-␥ (21,50). Human inflamed gingival tissue contains ␥␦ T cells expressing IFN-␥ mRNA (34,61).…”
Section: Discussionmentioning
confidence: 99%
“…During bacterial infection, the expression of CD64 on activated neutrophils was markedly increased (18,33,34). More important, it has also been shown that neutrophils of preterm infants expressed CD64 antigen to an extent similar to those of older children and adults (18).…”
Section: Diagnosis Of Neonatal Infection By Cd64mentioning
confidence: 98%
“…The expression of leukocyte cell-surface receptors was measured by flow cytometry as described earlier [22]. Briefly, aliquots of leukocyte suspension (containing 300,000 leukocytes) were labeled with fluorescein isothiocyanate (FITC)-conjugated anti-FcRIII (Caltag, San Francisco, CA), anti-CR1 (CLB, Amsterdam, The Netherlands), anti-L-selectin (Becton-Dickinson, San Jose, CA), and phycoerythrin (PE)-conjugated anti-FcRII (Caltag) and anti-CR3 (Becton-Dickinson) mAbs for 30 min at 4°C.…”
Section: Measurement Of Receptor Expressionmentioning
confidence: 99%